Pro environment personality of sex - survey results - Grochowska, Irena (Studia Ecologiae et Bioethicae, 2008)
After analysing the above answers we can deduct some results, which confirm certain behaviour in girls that can be scientifically explained. A survey helped in establishing ecological consciousness and was a help in characterizing a survival persona. Looking at the answers with inclusion of two different sexes we can follow differences in the views concerning environmental protection, the survey results clearly show a difference in approach to the natural environment depending on the sex. Women more clearly see the beauty, harmony and set order in the environment. Nature astonishes them and is a guarantee of life. Analysing the survey results it is not possible not to see the differences in viewing the natural environment. Quoting Estes we can say that mature woman (surviving woman) looking at a forest sees a home for herself and other people, whilst others looking at the same forest imagine cutting down trees and making money on it. Clean environment allowing life is like air necessary to live and you can only breathe deeply with clean air. It is similar with woman’s psyche where a mechanism of full breath operates and forces her to breathe in the fresh air. The research results confirmed that girls show more concern about harmony and complexity of the natural world and definitely at every opportunity become protectors of life. So a smaller extend that boys they support technological and technical development, they do not see it as a solution to problems connected with degradation of environment. If you would like to separate pro environment personality types taking into account these characteristic for boys and girls, based on the performed survey, we can present: Rational type , scientific thinker and technocrat, consumer, which is dominant in boys answers and emotional type, esthetic environmentalist which is dominant within girls answers. Woman can show man how to admire nature, how to develop sensitivity and open ones eyes to new perspectives, whose theoretical author is often he himself. It is women who with their hearts read and introduce into life philosophical life and written theological works whose authors are men. Woman’s task is activity connected with protecting the wisdom of soul, not to accept abnormal state for normal and to hale the courage to celebrate natural forces with elements of Her soul and life, which a priceless treasure of each woman. When women do not follow their voice when intervening in unacceptable situations her views fade, her nature fades and natural world. Love fades as well as the will to repair the world and harmony with nature, The Word lacks fresh air and water, but also the voice of consciousness. Research I have performed confirmed the thesis I had made and allows to precise the desired personality characteristics, needed to shape a survival personality.